Clinton's victory and us - Arias Quincot, César (1992)
The article begins with a look at the winning formula in last year's U.S. Presidential elections, in particular at the fact that the victors were two young men who prevailed through the fierce questioning of a generation which, despite being the most prosperous in the United States, still managed to doubt the injustices and failings of their society and their country's foreigns policy. It then gives a brief, historical account of the evolution of the US political system; the rise of the new right and the reaction to it: Clinton's victory. The final part of this study deals with our won situation: our inability to judge the international situation. In addition, the author examines our own historical authoritarian tendency which makes fruitful relations with our northern neighbour more difficult.